Vpliv delovnega okolja in življenjskega sloga na zadovoljstvo zaposlenih v športni infrastrukturi - Bon, Marta (Šport (Ljubljana), 2024)
The work environment can significantly impact the lifestyle of employees. The aim of the study was to investigate the lifestyle and satisfaction of employees at sport infrastructure. A questionnaire, available on the 1KA website, was sent to all employees. Data was collected via an online questionnaire and further analyzed using SPSS 21 (SPSS Inc., Armonk, New York, USA). Statistical analysis included the Mann-Whitney rank test, Kruskall-Wallis rank test, and Fisher’s exact test. 71 out of 122 employees participated, with an average age of 44.7 years. The results show that the majority of employees (60%) are physically active at least twice a week. Most of their activity lasts between 30 and 60 minutes (57%). They most often engage in walking, cycling, fitness, hiking, and running. Physical activity usually takes place in natural outdoor areas. At work, 60% of employees spend more than half of their time sitting. Job satisfaction was statistically significantly associated with satisfaction with family life (positive low correlation, p = 0.04), but not with a healthy lifestyle, sitting at work, physical activity, or monthly sports expenses. No differences were found in job satisfaction based on age or mode of transportation to work.
Keywords: delovno mesto; healthy lifestyle; sport; sport activity; šport; športna aktivnost; workplace satisfaction; zadovoljstvo na delovnem mestu; življenjski slog